Literatur Nilai-Nilai Islam Dalam Sistem Pendidikan - Abqari Agam; Quthni Poldi (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
In carrying out its social responsibilities, companies certainly want their programs to run according to what they planned. Each program implemented has certain objectives. These objectives can be in the form of benefits obtained by the local community, for example increasing knowledge through training, seminars or advertisements created by the company as a form of its CSR program. Apart from that, from the internal side of the company it is also possible to want to increase profits and gain a positive image from the CSR program. The community as recipients of CSR programs must of course be able to feel the benefits of the CSR program run by the company so that the program is able to promote positive things.